A modular low-cost atomic force microscope for precision mechatronics education. (June 2021) - Xia, Fangzhou; Quigley, James; Zhang, Xiaotong; Yang, Chen; Wang, Yi; Youcef-Toumi, Kamal
Abstract: Precision mechatronics and nanotechnology communities can both benefit from a course centered around an Atomic Force Microscope (AFM). Developing an AFM can provide precision mechatronics engineers with a valuable multidisciplinary hands-on training experience. In return, such expertise can be applied to the design and implementation of new precision instruments, which helps nanotechnology researchers make new scientific discoveries. However, existing AFMs are not suitable for mechatronics education due to their different original design intentions. Therefore, we address this challenge by developing an AFM intended for precision mechatronics education. This paper presents the design and implementation of an educational AFM and its corresponding precision mechatronics class. The modular educational AFM is low-cost ( ≤ 4, 000) and easy to operate. The cost reduction is enabled by new subsystem development of a buzzer-actuated scanner and demodulation electronics designed to interface with a myRIO data acquisition system. Moreover, the use of an active cantilever probe with piezoresistive sensing and thermomechanical actuation significantly reduced experiment setup overhead with improved operational safety. In the end, the developed AFM capabilities are demonstrated with imaging results. The paper also showcases the course design centered around selected subsystems. The new AFM design allows scientific-method-based learning, maximizes utilization of existing resources, and offers potential subsystem upgrades for high-end research applications. The presented instrument and course can help connect members of both the AFM and the mechatronics communities to further develop advanced techniques for new applications. Highlights: Modular low-cost educational Atomic Force Microscope design and implementation. Review of AFM related education and available platforms for various teaching purposes. Multi-actuated piezo buzzer AFM scanner and driver electronics development. Active AFM cantilever probe tapping mode electronics design for NI myRIO interface. Precision mechatronics course design centered around the proposed AFM platform.